It's not easy being mean : a Clique novel - Harrison, Lisi. (New York : Little, Brown, 2007)
While Massie and Alicia concentrate on finding the key to the secret room at Octavian Country Day School, Kristen struggles with new teammates, Dylan continues to obsess over her weight, and Claire questions the sacrifices she has to make to remain a Hollywood starlet.
Young Adult
Keywords: Cliques (Sociology) -- Fiction; Girls -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Private schools -- Fiction; Schools -- Fiction; Cliques (Sociology) -- Fiction; Girls -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Private schools -- Fiction; School stories; Westchester County (N.Y.) -- Fiction; Westchester County (N.Y.) -- Fiction